Managing business relationships (Chichester ; New York : John Wiley and Sons, 1998)
This book is about: Making sense of business markets; How companies relate to each other; The nature of management in business markets; Developing strategy in business markets; ...
Keywords: Business; Management; Strategic alliances (Business); Business networks